Integrated mapping of local mental health systems in Central Chile - Jose A. Salinas-Perez; Luis Salvador-Carulla; Sandra Saldivia; Pamela Grandon; Alberto Minoletti; Cristina Romero Lopez-Alberca (Pan American Health Organization, 2018)
Objective. To describe the availability of local mental health (MH) services in small MH catchment areas in Central Chile, using a bottom-up approach. Methods. MH services of 19 small MH catchment areas in five health districts of Central Chile that provide health care to more than 4 million inhabitants were assessed using DESDE-LTC (Description and Evaluation of Services and Directories in Europe for Long-Term Care), a tool for standardized description and classification of LTC health services, in a study conducted in 2012 ("DESDE-Chile") designed to complement other studies conducted in 2004 and 2012 at the national and regional level using the World Health Organization Assessment Instrument for Mental Health Systems (WHO-AIMS). Key informants from national, regional, and local health authorities were contacted to compile a comprehensive list of MH services or facilities (health, social services, education, employment, and housing). The analysis of local care provision covered three criteria-service availability, placement capacity, and workforce capacity. Results. The study detected disparities in all three criteria (availability and placement and workforce capacity) across the five health districts, between urban and rural areas, and between neighboring urban areas. Analysis of service availability revealed differences in the weight of residential services versus day and outpatient care. The Talcahuano area could be considered a benchmark of MH care in Central Chile, based on its service provision patterns, and the criteria of the community care model. The list of MH services identified in this study differed from the one generated in the 2012 WHO-AIMS study. Conclusions. This survey of local MH service provision in small catchment areas using the DESDE-LTC tool provided MH service provision data that complemented information collected in other studies conducted at the national/regional level using the WHO-AIMS tool. The bottom-up approach applied in this study would also be useful for the assessment of equity and accessibility and local planning.